2022
DOI: 10.7759/cureus.29135
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19 on Physicians’ Perceived Ability to Provide Care for Patients With Type II Diabetes Mellitus

Abstract: Background and objectiveThe coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), presents multiple, diverse challenges to providing appropriate medical care, especially in terms of medication and treatment adherence for chronic diseases such as type 2 diabetes mellitus (T2DM). The COVID-19 pandemic has exacerbated these barriers by potentially forcing physicians to modify their treatment plans due to limitations on in-person visits and changes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The average duration of telediabetes engagement was much higher at 3.5 hours per day at the peak of the COVID-19 wave in mid-2021, compared to one hour after the ease of the wave, attributable to the stringent restrictive measures implemented during the wave, which made accessing healthcare facilities difficult along with apprehension among the public. The conversion of many healthcare facilities into specialized COVID care centers to tackle the urgent burden of the pandemic further accentuated these issues during the peak pandemic months [ 10 , 11 ]. Video calling, voice calling, and messaging were the modalities of communication used for delivering the teleconsultations in order of preference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average duration of telediabetes engagement was much higher at 3.5 hours per day at the peak of the COVID-19 wave in mid-2021, compared to one hour after the ease of the wave, attributable to the stringent restrictive measures implemented during the wave, which made accessing healthcare facilities difficult along with apprehension among the public. The conversion of many healthcare facilities into specialized COVID care centers to tackle the urgent burden of the pandemic further accentuated these issues during the peak pandemic months [ 10 , 11 ]. Video calling, voice calling, and messaging were the modalities of communication used for delivering the teleconsultations in order of preference.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of physical examinations, leading to a difficulty in diagnosis (92.3%) and difficulty in the management of acute conditions (72.3%), was perceived as disadvantages, observations which are in accordance with the findings of earlier studies, such as that conducted by Naik et al [ 19 ] The overall perception towards telediabetes was either positive (50.1%) or neutral (30.3%). In the study by Abidi et al [ 10 ], the main issues with telediabetes that were identified included the lack of a regular physical exam, which is perceived to be necessary to properly treat patients (78.4%) (n=65), and 48.2% did not believe that a more complete picture of the case was not available with remote consultations. In terms of satisfaction, 47.0% (n=39) were not as satisfied with remote consultations as with face-to-face patient visits.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the results of the study by Coma showed that during CoVid-19, patients' visits to primary care doctors decreased by 50% [17], the reasons for which could be the change in the patients' health behaviour due to the fear of contracting CoVid-19 and the social distancing measures that caused barriers to access to clinics. according to the study by abidi, CoVid-19 had a negative impact on continuous in-person examinations of diabetic patients [22]. another study conducted in Canada showed that in-person visits to specialist doctors decreased by 7.7% during the pandemic [23].…”
Section: Discussionmentioning
confidence: 99%